2019
DOI: 10.1039/c9nj02471a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure, DFT calculations, protein interaction, anticancer potential and bromoperoxidase mimicking activity of oxidoalkoxidovanadium(v) complexes

Abstract: Intriguing structure–activity relationships (SARs) indicating an apparent dependence of anticancer and haloperoxidase activities on the carbon chain length of the alkoxo group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…To synthesize dipicolinate vanadium­(IV) complexes [VO­(dipic)­(N ∩ N)], the procedure based on the reaction of [VO­(dipic)­(H 2 O) 2 ] with an appropriate N-donor ligand was employed. The vanadium­(IV) precursor [VO­(dipic)­(H 2 O) 2 ] was obtained according to the literature method based on the reaction of vanadyl sulfate with dipicolinic acid. , Identity and purity of [VO­(dipic)­(N ∩ N)] were confirmed by elemental analysis, FT-IR technique, X-ray analysis, UV–vis, and EPR spectroscopies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize dipicolinate vanadium­(IV) complexes [VO­(dipic)­(N ∩ N)], the procedure based on the reaction of [VO­(dipic)­(H 2 O) 2 ] with an appropriate N-donor ligand was employed. The vanadium­(IV) precursor [VO­(dipic)­(H 2 O) 2 ] was obtained according to the literature method based on the reaction of vanadyl sulfate with dipicolinic acid. , Identity and purity of [VO­(dipic)­(N ∩ N)] were confirmed by elemental analysis, FT-IR technique, X-ray analysis, UV–vis, and EPR spectroscopies.…”
Section: Resultsmentioning
confidence: 99%
“…4,7-Phenothiazine-1,10-phenanthroline, 121 [VO(dipic)(H 2 O) 2 ], 39,56 [VO(dipic)(phen)], 57−59 [VO(dipic)(bipy)], 59,60 and [VO(dipic)-(im) 2 ] 39 were prepared according to a procedure described in the literature, and their analytical data provided a good agreement with those reported in refs 39, 56−60, 121. 39,[56][57][58][59][60]121 Synthesis of [VO(dipic)(N ∩ N)]. The complex [VO(dipic)-(H 2 O) 2 ] (1 mmol) and appropriate diamine ligand (1 mmol) were dissolved in methanol (30 mL), and the resulting solution was refluxed under argon for 6 h. After cooling to room temperature, the precipitate of [VO(dipic)(N ∩ N)] was collected by filtration and dried in air.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The ground state geometry of the complex was fully optimized in gas phase using B3LYP and LanL2DZ basis sets. The optimized geometry of complex found to be octahedral based on bond angle and bond length obtained from DFT calculation [35] . Selected bond lengths and bond angles of complex are listed in table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The use of V-based compounds offers many benefits such as easy synthesis, relatively low cost and low toxicity, high bioavailability, and high selectivity toward cancer cells. , Furthermore, vanadium can readily expand its coordination sphere and easily switch between different oxidation states V­(III), V­(IV), and V­(V) in biological systems, which probably plays important roles in the biological effects of vanadium compounds as potential therapeutic agents. , Many new vanadium-based complexes thus have been constantly explored as potential chemotherapeutic agents for cancer treatments since Krahl et al reported the antitumor activity of the first vanadium derivative vanadocene dichloride against Ehrlich cancer in 1983 (Figure ). For example, Dinda et al have recently synthesized an ethoxido-bridged dinuclear oxidovanadium­(IV) complex with 2-arylazophenol ligands as potential anticancer agents against HeLa cells. Very recently, new mononuclear oxidovanadium­(IV) complexes were developed by Lord et al and Chakrabarti et al, which are cytotoxic toward different cancerous cell lines yet have lower potency against normal cell types.…”
Section: Introductionmentioning
confidence: 99%
“… For example, Dinda et al have recently synthesized an ethoxido-bridged dinuclear oxidovanadium­(IV) complex with 2-arylazophenol ligands as potential anticancer agents against HeLa cells. Very recently, new mononuclear oxidovanadium­(IV) complexes were developed by Lord et al and Chakrabarti et al, which are cytotoxic toward different cancerous cell lines yet have lower potency against normal cell types. Afterward, the DNA binding activities, cell cycle, and apoptosis for some non-oxidovanadium­(IV) complexes , and oxidovanadium­(IV) complexes , have also been examined.…”
Section: Introductionmentioning
confidence: 99%